(untitled) (International journal of artificial intelligence, 2025)
The development of professional competence in foreign language teachers is a multifaceted process that involves the enhancement of linguistic, pedagogical, and cultural proficiency. This study aims to explore the methodology for fostering the professional competence of foreign language teachers through targeted strategies such as continuous professional development, reflective practices, and the integration of modern technological tools. Emphasizing a holistic approach, the research investigates key components such as content knowledge, pedagogical skills, and intercultural awareness, which are essential for effective language instruction. Furthermore, the paper examines the role of teacher education programs, in-service training, and collaborative learning environments in enhancing teacher competencies. The findings underscore the need for a dynamic and adaptive methodology that addresses the evolving demands of language teaching, fostering lifelong learning, and ensuring quality education.